Aplikasi Warna Marawa pada Busana Kontemporer - Azka Haniyah Putri; Mirda Aryadi; Nofi Rahmanita; Dini Yanuarmi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The work entitled "Application of Marawa Colors in Contemporary Fashion" is inspired by the colors of the Marawa, a traditional cultural symbol of the Minangkabau community. The contemporary garments feature asymmetric silhouettes designed with a simple yet elegant appearance. The arrangement of the Marawa colors is visually represented through the composition of fringes made from yarn, creating a distinctive decorative element. The designs incorporate layered contemporary garments combined with Silungkang woven songket fabric. The color palette follows the traditional Marawa colors black, red, and yellow using cotton drill, premium cotton, Ima cotton, and Silungkang songket as the primary materials. The creative process began with collecting references related to the design concept, followed by concept development, field observation, and the formulation of the creative idea. This collection was developed based on the Trend Forecasting 2026/2027 theme "Fringe", which emphasizes garments featuring fringe details. The use of materials such as strands of yarn, cords, tassels, and similar decorative elements characterizes this trend. In this collection, fringe is interpreted through the application of fringes and tassel embellishments combined with dangling beads, and further enriched with sashiko embroidery and bead embroidery techniques